A Novel Type of Tetradentate Dipyridyl-Derived Bis(pyrazole) Ligands for Highly Efficient and Selective Extraction of Am3+ Over Eu3+ From HNO3 Solution. Issue 2 (23rd February 2023) - Song, Lianjun; Wang, Xueyu; Li, Long; Wang, Zhuang; He, Lanlan; Li, Qiuju; Pan, Qingjiang; Ding, Songdong
ABSTRACT: The extraction of Am 3+ and Eu 3+ with 6, 6'-bis(5-alkyl-1 H -pyrazol-3-yl)-2, 2'-bipyridine (BPzBPy, alkyl = i-Bu, n-Bu, n-Oct) from HNO3 medium and the complexation of BPzBPy with Eu 3+ were investigated. By using meta -nitrobenzotrifluoride (F-3) as a diluent, iBu-BPzBPy ligand in combination with 2-bromohexanoic acid was able to extract Am 3+ over Eu 3+ with the nature of significantly high efficiency, relatively fast extraction kinetics, and easy stripping. Slope analysis showed the formation of a 1:2 metal/ligand extraction species. The analyses of electrospray ionization mass spectrometry (ESI-MS), Fourier transform infrared (FT-IR) and time-resolved laser fluorescence spectrum (TRLFS) revealed that the composition of the extracted complex was [Eu(H2 O)L2 ]A3 (L = ligand; HA = 2-bromohexanoic acid). The complexation of iBu-BPzBPy ligand with Eu 3+ was an enthalpy-driven spontaneous, exothermic, and entropy-decreasing process. Besides, the complex stability constants were also obtained via UV–vis spectrophotometric titration. Combining the results of solvent extraction and complexation studies, a cation exchange extraction model was also proposed. GRAPHICAL ABSTRACT: uf0001